Regiony słabo rozwinięte w polityce strukturalnej Unii Europejskiej - Cybulski, Leszek (Less Developed Regions in the Cohesion Policy in the EU, 2006)
The policy towards the less developed regions is the most important part of the structural policy in the EU. The financial aspect is crucial for the characteristics of those regions in different budget periods 1988-2013. The number of these regions rises as the consequence of the economic processes, administration reform, political games and first of all the enlargement of the EU. There is not many information about the changes of the number of the regions in T l, so the aim of this paper is to make a synthesis and description of the changes in the period 1988-2006 and the general evaluation of the cohesion and quality of the projects for the period 2007-2013.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 348-373